An investigation on internal lightweight load bearing structures - Toh, William (2020)
This paper investigates the differences in structural response of lightweight internal structures using finite element (FE) simulation to provide quantitative comparison of the advantages of each type of structure. Various configurations, corresponding to different amounts of weight savings, were studied under distributed pressure loading and bending moment loading conditions. It was found that for configurations with less weight savings, the kagome possesses better performance than the honeycomb structure. However, as the amount of weight savings increases, the trend was observed to be reversed, with the honeycomb structure providing much better performance than the kagome structure. In general, it was shown that the honeycomb structure possesses better performance than the kagome structure under cantilever loading conditions.